1969
DOI: 10.1007/bf02531006
|View full text |Cite
|
Sign up to set email alerts
|

Microbial hydration ofCis‐9‐alkenoic acids

Abstract: The activity of acis‐9‐fatty acid hydratase produced by aPseudomonas sp. (NRRL B‐3266) isolated from soil was compared with that of another isolate previously reported (NRRL B‐2994). The presence of appropriate fatty acids for at least 4 hr during aerobic growth in yeast extract medium increased subsequent enzyme activity. Such cells anaerobically hydrated severalcis‐9‐alkenoic acids to 10‐hydroxy fatty acids and aerobically formed 10‐keto acids, which were partially degraded to shorter chain keto acids. Melti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Pseudomonas strain NRRL-B-3266 [3], Acetobacterium woodii [4], Nocardia cholesterolicum [5], a Flavobacterium sp. [6], Lactobacillus plantarum [8] and an extract from Pseudomonas strain NRRL-B-2994 [7] have been shown to convert linoleic acid to 10-hydroxy-12-octadecenoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas strain NRRL-B-3266 [3], Acetobacterium woodii [4], Nocardia cholesterolicum [5], a Flavobacterium sp. [6], Lactobacillus plantarum [8] and an extract from Pseudomonas strain NRRL-B-2994 [7] have been shown to convert linoleic acid to 10-hydroxy-12-octadecenoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The Pseudomonas studied by Davis et al (1969) was also able to perform this reaction, but it has not previously been reported in intestinal bacteria. Unlike the Pseudomonas, however, none of the intestinal bacteria tested was able to hydrate linoleic acid, to form an unsaturated hydroxyacid similar to ricinoleic acid.…”
Section: Discussionmentioning
confidence: 93%
“…This indicates strongly that the product was an hydroxypalmitic acid with the hydroxyl group on one of the carbon atoms from 5 to 13 (Tulloch, 1964). Although the position of the hydroxyl group was not determined, in the only other report of an hydroxypalmitic acid formed from palmitoleic acid by a micro-organism this was stated to be 10-hydroxypalmitic (Davis et al, 1969). It is therefore assumed that the product formed by intestinal bacteria is probably 10-hydroxypalmitic.…”
Section: Bacteroides Spp Bifidobacteria Enterococcimentioning
confidence: 98%
“…The oil did not respond to Halphen [6] and picric acid TLC [7] tests indicating the absence of cyclopropenoid and epoxy fatty acids, respectively. However, the oil responded to the DNPH test [8] showing the presence of a keto group. Methyl esters were prepared by refluxing the oil in methanol in acidic medium [9].…”
Section: Methodsmentioning
confidence: 99%